An allosteric modulator binds to a conformational hub in the beta(2) adrenergic receptor - Liu, Xiangyu; Kaindl, Jonas; Korczynska, Magdalena; Stößel, Anne; Dengler, Daniela; Stanek, Markus; Hübner, Harald; Clark, Mary J.; Mahoney, Jake; Matt, Rachel Ann; Xu, Xinyu; Hirata, Kunio; et al. (Nature Chemical Biology, 2020)
Most drugs acting on G-protein-coupled receptors target the orthosteric binding pocket where the native hormone or neurotransmitter binds. There is much interest in finding allosteric ligands for these targets because they modulate physiologic signaling and promise to be more selective than orthosteric ligands. Here we describe a newly developed allosteric modulator of the beta(2)-adrenergic receptor (beta(2)AR), AS408, that binds to the membrane-facing surface of transmembrane segments 3 and 5, as revealed by X-ray crystallography. AS408 disrupts a water-mediated polar network involving E122(3.41) and the backbone carbonyls of V206(5.45) and S207(5.46). The AS408 binding site is adjacent to a previously identified molecular switch for beta(2)AR activation formed by I-3.40, P-5.50 and F-6.44. The structure reveals how AS408 stabilizes the inactive conformation of this switch, thereby acting as a negative allosteric modulator for agonists and positive allosteric modulator for inverse agonists.
CRIS-Team WoS Importer:2020-06-16